Occupational Health and Safety (OHS) Training for Expedition Couriers to be Able to Deal with Multi-Hazards (International Journal of Active Learning, 2022)
Fatigue is a problem that can occur in every workforce that is closely related to decreased performance and productivity. Work fatigue is defined as a process of decreasing efficiency, work performance, and reduced physical strength or endurance to continue activities, the decline in the health condition of workers can trigger work accidents and work-related diseases. This study aims to determine the association between workload, length of work, length of work, exercise habits and age with work fatigue. The type of research used is quantitative research which is analytic with a cross sectional approach. The population in this study were ID Express Drop Point Kroya expedition couriers, Cilacap Regency, totaling 40 people. The sample for this study was all package delivery workers or couriers working at ID Express Drop Point Kroya with a total of 35 people, using a total sampling technique. Data were analyzed by univariate and bivariate. The results showed that workload (p=0.024), years of service (p=0.027), length of work (p=0.007), and exercise habits (p=0.021) were associated with work fatigue on expedition courier ID Express Drop Point Kroya, Cilacap Regency.